Integral field spectroscopy of HII regions in M33 - López Hernández, Jesús (2013)
Integral field spectroscopy is presented for star-forming regions in M33. A central area of 300 × 500 pc2 and the external H II region IC 132, at a galactocentric distance ∼19 arcmin (4.69 kpc), were observed with the Potsdam Multi-Aperture Spectrophotometer instrument at the 3.5-m telescope of the Centro Astronómico Hispano–Alemán (CAHA, aka Calar Alto Observatory). The spectral coverage goes from 3600 Å to 1 μm to include from [O II] λ3727 Å to the near-infrared lines required for deriving sulphur electron temperature and abundance diagnostics. Local conditions within individual H II regions are presented in the form of emission-line fluxes and physical conditions for each spatial resolution element (spaxel) and for segments with similar Hα surface brightness. A clear dichotomy is observed when comparing the central to outer disc H II regions. While the external H II region has higher electron temperature plus larger Hβ equivalent width, size and excitation, the central region has higher extinction and metal content. The dichotomy extends to the Baldwin–Phillips–Terlevich (BPT) diagnostic diagrams that show two orthogonal broad distributions of points. By comparing with pseudo-3D photoionization models, we conclude that the bulk of observed differences are probably related to a different ionization parameter and metallicity. Wolf–Rayet (WR) features are detected in IC 132, and resolved into two concentrations whose integrated spectra were used to estimate the characteristic number of WR stars. No WR features were detected in the central H II regions despite their higher metallicity.